COMMERCIAL CARCASS FAT AND NON-CARCASS FAT DEPOSITS IN THE ADMINISTRATION OF MINERALS (ZN) AND AMINO ACIDS (METHIONINE, LYSINE, AND L-CARNITINE) TO LAMB MEAT - Korima, Inge; Mansyur, Mansyur; Indiriani, Nyimas Popi; Ramadhan, Rahmad Fani; Hidayat, Rahmat (Fakultas Peternakan, Universitas Padjadjaran, 2025)
The increasing demand for meat must be accompanied by an increase in the production of fattening sheep. One of the local sheep whose meat is used is the Priangan sheep. The demand for meat is not only the quantity but also the quality of the meat, which influences consumer interest. Low-fat is the consumer's choice when choosing meat. This research aims to test the effect of providing minerals (Zink) and amino acids (Methionine, Lysine, and L-Carnitine) on commercial carcass fat and non-carcass fat. The livestock used were 20 7-month-old Priangan sheep with an average weight of 14.66 kg. Maintenance was for 67 days, of which 7 days were adapted and 60 days were treated. The statistical analysis used was a completely randomized design (CRD) of 4 treatments with 5 replications. If the statistical results show that there is an effect of treatment (P<0.05), then a further test is carried out using the Duncan Test. The treatments observed were (P1): No Treatment, (P2): Giving Zn (60 mg), (P3): Giving Zn (60 mg) + Methionine (3 g) + Lysine (5 g), and (P4): Administration of Zn (60 mg) + Methionine (3 g) + Lysine (5 g) + L-Carnitine (200 ppm). The results showed that the addition of Zn (60 mg) had an effect on carcass fat (back, stomach, right loin, and neck fat), while non-carcass fat components had no effect.